PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, TRANSAKSIONAL, KEPUASAN KERJA TERHADAP OCB KARYAWAN PT.KONSTRINDO PUTERA PERKASA - Idris, Batara Ariansyah Indra; Azis, Azis; Kornelius, Yobert (Jurnal Ilmu Manajemen Universitas Tadulako (JIMUT), 2016)
This study aims to find out Transformational Leadership Style, Transactional Leadership Style and Job Satisfaction have influence, either simultaneously or partially, to Organizational Citizenship Behavior (OCB) Employee PT.Konstrindo Putera Perkasa. The sample in this study using all the population with the method used is saturated or census sampling. Data collection was done by using questionnaires, interviews, and through observation (observation). This study uses Multiple Linear Regression Analysis Method with the help of computer program SPSS For Windows Release 17.0.The result of hypothesis analysis and testing can be concluded that: (1) based on results obtained by Sig.F 0.000 <0,05, which can be interpreted that the variables of transformational leadership style, transactional leadership style and job satisfaction simultaneously affect the Organizational Citizenship Behavior (OCB) variable. (2) based on the regression test results, the variables of transformational leadership style have significance level t sig. (0,000) <Î± (0,05), transactional leadership style variable has significance level t sig. (0.019) <Î± (0,05) and job satisfaction variable have significance level t sig. (0,05) <Î± (0,05), so that variable of transformational leadership style, transactional leadership style and satisfaction of work partially influence to organizational citizenship Behavior (OCB) variable (3) based on result of regression test obtained variable which influenced most dominant is transformational leadership style has the highest Beta value is 0.708.Â Penelitian ini bertujuan untuk mengetahui Gaya Kepemimpinan Transformasional ,Gaya Kepemimpinan Transaksional dan Kepuasan Kerja mempunyai pengaruh, baik secara simultan maupun secara parsial, terhadap Organizational Citizenship Behavior (OCB)Â  Karyawan PT.Konstrindo Putera Perkasa, Sampel dalam penelitian ini menggunakan seluruh populasi dengan metode yang digunakan yaitu sampling jenuh atau sensus. Pengumpulan data dilakukan dengan menggunakan kuesioner, wawancara, dan melalui pengamatan (observasi). Penelitian ini menggunakan Metode Analisis Regresi Linear Berganda dengan bantuan program komputer SPSS For Windows Release 17.0. Hasil analisis Uji F disimpulkan bahwa variabel gaya kepemimpinan transformasional, gaya kepemimpinan transaksional dan kepuasan kerja secara serempak berpengaruh terhadap variabel Organizational Citizenship Behavior (OCB) sedangkan Uji T disimpulkan variabel gaya kepemimpinan transformasional, gaya kepemimpinan transaksional dan kepuasan kerja secara parsial berpengaruh terhadapvariabel Organizational Citizenship Behavior (OCB).